2018
DOI: 10.1177/0269215518819701
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of falls after stroke: a 12-month follow-up of 490 patients in The Fall Study of Gothenburg (FallsGOT)

Abstract: Objective: To identify the incidence of falls and factors present shortly after stroke, which are associated with the occurrence of falls over the first 12 months after stroke onset, following discharge from inpatient rehabilitation. Design: Prospective follow-up study. Setting: Stroke unit and outpatient department. Subjects: A total of 490 individuals with acute stroke. Methods: Postural control was assessed using the Swedish modified version of the Postural Assessment Scale for Stroke Patients. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…It has been shown that the risk for falls is high during all stages post stroke (27). However, most falls occur during the first months after stroke onset (50). In order to reduce the number of falls, it is important to identify persons at risk as early as possible after stroke onset.…”
Section: Risk Factors For Fallsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the risk for falls is high during all stages post stroke (27). However, most falls occur during the first months after stroke onset (50). In order to reduce the number of falls, it is important to identify persons at risk as early as possible after stroke onset.…”
Section: Risk Factors For Fallsmentioning
confidence: 99%
“…Other tests assess the attentional and proactive gait control-demanding task of negotiating and crossing obstacles while walking (79,(84)(85)(86), but these tests cannot be performed when walking aids are used. Since persons with stroke commonly use walking aids (50), it is important to develop reliable and valid assessments of obstacle avoidance for persons with stroke (87) and to assess the predictive value for future falls of such tests. To fill this gap, HS and colleagues developed the Cone Evasion Walk test (CEW) (88).…”
Section: Obstacle Avoidance and Attention During Gait Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls are common in stroke survivors, with reported incidences between 26% to 73% within 6‐12 months after discharge from hospital 1‐3 and 23% to 48% of community dwelling older people who fall within a 1‐year period after acute hospitalization 3‐6 . Falls on inpatient stroke rehabilitation units are also common, 5‐9 with 15% to 37% of patients experiencing a fall during their inpatient stay 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…3 Approximately 25% to 46% of all patients in stroke rehabilitation wards have been reported to fall at least once during their stay. [4][5][6] Alarmingly, 75% of deaths in the age group of 65þ in the USA are caused by falls, 2 thus concerning 13% of the country's population. In different regions including Europe, USA, and Australia, between 0.9% and 1.5% of the total health care expenditures of each region are related to fall.…”
Section: Introductionmentioning
confidence: 99%